Foreign and second language learning : language-acquisition research and its implications for the classroom - Littlewood, William (New York : Cambridge University Press, 1984)
Discusses studies and ideas to improve the teaching and learning of foreign and second languages, examining different language theories, whether language learners can be predisposed to approach languages in a certain order, why some individuals are more successful at language acquisition than others, and other related topics.
Includes bibliographical references (p. 100-112) and index.
Professional
Keywords: Language and languages -- Study and teaching -- Psychological aspects; Learning, Psychology of; Second language acquisition; Language and languages -- Study and teaching -- Psychological aspects; Psychology of learning